The implications of an aging population and increased obesity for knee arthroplasty rates in Sweden: a register-based study. (7th September 2020) - Overgaard, Anders; Frederiksen, Peder; Kristensen, Lars Erik; Robertsson, Otto; W-Dahl, Annette
Abstract : Background and purpose — Total knee arthroplasty (TKA) has increased substantially in Sweden. We quantified the relative risk for TKA in the Swedish population for different BMI categories and age groups to investigate whether the continued increase in TKA is attributable to increased prevalence of obesity and elderly people in the population, and to put forward model predictions for coming needs for TKA. Patients and methods — We used the Swedish Nationwide Health Survey (SNHS) and the Swedish Knee Arthroplasty Register (SKAR) 2009–2015 to calculate the relative risk (RR) of TKA by age (middle-aged 45–64 years and elderly 65–84 years) and BMI (BMI 18.5–24.9 normal weight; BMI 25.0–29.9 overweight; BMI > 30 obese). The RR for TKA was applied to the demographic forecasts for the Swedish population as a forecasting model. Results — Population size increased 5.2% from 2009 to 2015 to 40, 000 middle-aged and 250, 000 elderly, and the prevalence of obesity increased from 16% to 18% in these 2 age categories. Compared with those of normal weight, the RR for TKA was 2.7 (95% CI 2.5–3.0) higher for the overweight and 7.3 (6.7–8.0) higher for the obese, aged 45–64. The corresponding figures for individuals aged 65–84 were 2.1 (2.0–2.2) and 4.0 (3.8–4.3) higher, respectively. The changes in the prevalence of obesity and an increase in the elderly population accounted for an estimated increase of 1, 700 TKAs over the 7 years. Interpretation — The increase in obesity frequency and the rise in the population of middle-aged and elderly may, to some extent, explain the rise in TKA utilization in Sweden.